143k views
0 votes
Find the solution of the given initial value problem in explicit form. y' = (1 – 11x)y?, y(0) = -1 Enclose numerators and denominators in parentheses. For example, (a - b)/(1 + n). y(x) = Q

User Seifolahi
by
5.8k points

1 Answer

3 votes

Answer:


y(x)=-e^{x-((11*x^(2) )/(2)) }

Explanation:

This is a separable equation. First divide both sides by y:


(dy(x))/((dx)/(y(x)) ) =-11x+1\\(dy)/(y)=(-11x+1)dx

Integrate both sides:


\int\ (dy)/(y) \ =\int\ (-11x+1) \, dx


log(y)=-((11*x)/(2) )+x+ c_1

Solve for y taking exp to both sides:


y(x)=c_1*e^{x-((11*x^(2) )/(2)) }

Where
c_1 is an arbitrary constant

Evaluating the initial condition:


y(0)=c_1*e^{0-((11*0^(2) )/(2)) } =-1


c_1*e^(0) =-1\\c_1*1=-1\\c_1=-1

Finally, replacing
c_1 in the differential equation solution:


y(x)=-e^{x-((11*x^(2) )/(2)) }

User Miguel Ferreira
by
5.4k points